2021
DOI: 10.4081/jphr.2021.2359
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Injury and its Determinants among Adolescents

Abstract: Background: Globally, unintentional injury has been a documented public health problem among adolescents having debilitating consequences and accountable for economic burden. The study was undertaken to estimate the prevalence of unintentional injury, identify the determinants and consequences among adolescents.Design and Methods: This cross-sectional study recruited 222 adolescents using systematic random sampling from a site covered under UHTC Srinagar Garhwal, Uttarkhand. Binary and multivariate logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
7
3
3
Order By: Relevance
“…Another important risk factor identi ed by Reddy et al [22] was smoking though insigni cant statistically, on the contrary in our study smokers had a 12.8 higher incidence of total unintentional injuries compared to non-smoker (P <0.001) when adjusted for age and sex. Other risk factors identi ed by Reddy et al [22] were overcrowding [27]. This is similar to our study, which showed that youth with > 8 family members had higher incidence of total expected injuries when adjusted for age and sex (P=0.002).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another important risk factor identi ed by Reddy et al [22] was smoking though insigni cant statistically, on the contrary in our study smokers had a 12.8 higher incidence of total unintentional injuries compared to non-smoker (P <0.001) when adjusted for age and sex. Other risk factors identi ed by Reddy et al [22] were overcrowding [27]. This is similar to our study, which showed that youth with > 8 family members had higher incidence of total expected injuries when adjusted for age and sex (P=0.002).…”
Section: Discussionsupporting
confidence: 92%
“…India being a neighboring South Asian country has demographic similarities with Pakistan. An epidemiologic survey done on the adolescent population from India, by Reddy et al in 2021 [27], showed that 73% of the adolescents sampled had unintentional injuries [27], this is similar to our study where 503 injuries were reported which is approximately I injury per participant (N=547). Reddy et al reported male sex as a statistically insigni cant risk factor with OR of 1.0, this is contrary to our study where males had 1.6 times higher incidence for total unintentional injuries, with a statistical signi cance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Drawn from the SEM, the findings suggest that some personal and psychosocial factors emerged as significant predictors with increased odds of serious unintentional injuries among in-school adolescents in SVG. Specifically, corroborating earlier investigations, 6,12,13,24 the current analysis found higher odds (1.245) of severe injuries among males than females, after adjusting for other factors. Varying empirical perspectives exist concerning the role of gender in the occurrence of injuries.…”
Section: Discussionsupporting
confidence: 91%
“…In 2018, a similar rate was reported in a study conducted in India assessing the risk behaviors of unintentional injuries among school-aged adolescent boys, and among the participants, only 11.9% reported sustaining a serious unintentional injury in the past 12 months [22]. In comparison, higher prevalence rates were reported in multiple other studies [23,24]. Differences in population settings and external environmental factors could explain the observed differences in the prevalence rates.…”
Section: Discussionsupporting
confidence: 58%